2017
DOI: 10.1093/hmg/ddx157
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in THAP11 cause an inborn error of cobalamin metabolism and developmental abnormalities

Abstract: CblX (MIM309541) is an X-linked recessive disorder characterized by defects in cobalamin (vitamin B12) metabolism and other developmental defects. Mutations in HCFC1, a transcriptional co-regulator which interacts with multiple transcription factors, have been associated with cblX. HCFC1 regulates cobalamin metabolism via the regulation of MMACHC expression through its interaction with THAP11, a THAP domain-containing transcription factor. The HCFC1/THAP11 complex potentially regulates genes involved in divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 35 publications
6
66
1
Order By: Relevance
“…During the course of this study, a human THAP11 mutation was identified in a patient with cobalamin disorder [22]. We thus took advantage of this finding to focus, as we do in the remainder of this study, on the clarification of the functional consequences of this cobalamin-disorder-associated THAP11 F80L mutation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the course of this study, a human THAP11 mutation was identified in a patient with cobalamin disorder [22]. We thus took advantage of this finding to focus, as we do in the remainder of this study, on the clarification of the functional consequences of this cobalamin-disorder-associated THAP11 F80L mutation.…”
Section: Resultsmentioning
confidence: 99%
“…We thus took advantage of this finding to focus, as we do in the remainder of this study, on the clarification of the functional consequences of this cobalamin-disorder-associated THAP11 F80L mutation. The THAP11 F80 phenylalanine residue is highly conserved across vertebrate species [22] and also among the 12 different human THAP proteins (S1 Fig). As labeled in blue in S1 Fig, it is at the last position of the so-called “AVPTI F ” box (green box in S1 Fig) lying at the C terminus of the THAP-domain; this box has been suggested to promote proper folding of the DNA-binding zinc finger [3,4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA recognition sequence of Ronin is frequently found in chromatin loop anchors (Bailey et al, 2015), making it conceivable that some of its actions may be exerted through changes in the 3D genomic organization of promoters. Ronin's gene regulation and DNA recognition sequence have been critically linked to heart development (Fujita et al, 2027), retina development (Poche et al, 2016) and disease (Radziwon et al, 2017) as well as cobalamin metabolism (Quintana et al, 2017). Additionally, polyglutamine proteins such as Ronin have recently been associated with the assembly of functional units (e.g., Pol II) through a biophysical process called phase separation (Toretsky and Wright, 2014).…”
Section: We Herein Show That An Increase In Ronin Activity In Cerebelmentioning
confidence: 99%